2021
DOI: 10.1016/j.heliyon.2021.e06664
|View full text |Cite
|
Sign up to set email alerts
|

EFL college junior and senior students' self-regulated motivation for improving English speaking: A survey study

Abstract: Despite majoring in English, many junior and senior college students face limited opportunities to practice their EFL speaking in class. Some self-motivated students, through self-regulated learning, seek beyond-class opportunities to tap into physical and virtual human interaction to hone their spoken English. This study examined junior and senior college students' level of self-regulated motivation to improve their speaking of English as a foreign language (SRMIS-EFL). It looked into the interaction of stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 52 publications
(205 reference statements)
1
19
1
Order By: Relevance
“…The same finding was also recorded in the study by Boran and Karakus (2022), involving gifted and talented school students whose high metacognitive awareness significantly affected their problem-solving skills directly displayed in many creative solutions. Similarly, a high level of motivation self-regulation strategies among Yemeni college seniors was uncovered by Alotumi (2021). Thus, drawing on the first finding of the present study and those of previous research, it can be inductively concluded that self-regulated learning strategies are essentially and beneficially grown with learners' educational advancements over the years across cultures, disciplines, and learning contexts.…”
Section: Discussion and Implicationsupporting
confidence: 74%
See 2 more Smart Citations
“…The same finding was also recorded in the study by Boran and Karakus (2022), involving gifted and talented school students whose high metacognitive awareness significantly affected their problem-solving skills directly displayed in many creative solutions. Similarly, a high level of motivation self-regulation strategies among Yemeni college seniors was uncovered by Alotumi (2021). Thus, drawing on the first finding of the present study and those of previous research, it can be inductively concluded that self-regulated learning strategies are essentially and beneficially grown with learners' educational advancements over the years across cultures, disciplines, and learning contexts.…”
Section: Discussion and Implicationsupporting
confidence: 74%
“…This symmetric relation between the two components (intellectual operations) is also reported in past research. For instance, the levels of affect regulation and classroom environment regulation to enhance English speaking performances were both high (Alotumi, 2021;Uztosun, 2020). When self-regulated learning strategies increased, there was a positively corresponding increase in reading comrehension skills (Amini et al, 2020;Yaghi (2021), in listening comprehensions skills (Nosratinia et al, 2015;Yang, 2020), and in writing skills as well (Sun & Wang, 2020;Teng & Zhang, 2020).…”
Section: Discussion and Implicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-linguistic aspect becomes an additional factor the Indonesian students run into to develop their speaking skill. Those problems can be caused by several factors, problems that may arise can be in the form of a sense of excessive anxiety (Alotumi, 2021;Sholikhi, 2021) caused by poorly preparation. Feeling of fear of making mistakes can also cause problems for students in conducting verbal communication activities using English.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In order to attain academic goals, many students study English (Business English) classes to enhance their business communication skills (Pandeeswari, Hariharasudan & Nawaz, 2021). The highest academic achievers are effective communicators in Business English because academic success is heavily dependent on business communication ability (Alotumi, 2021;Rahiman et al, 2020). As a result, students have a wide range of expectations for how they will be taught English.…”
Section: Introductionmentioning
confidence: 99%